Bläckfläckar blir till något mer : En kvalitativ undersökning om textsamtal i lågstadiet avseende skönlitterära texter - Larsson, Emma (2016)
The purpose of this study is to contribute with increased understanding and knowledge about text conversations concerning fiction. The aim of this study is partly to increase knowledge about which skills pupils can develop through text conversations about fiction, partly to give insight about teachers’ knowledge about the configuration form text conversations about fiction, and pupils’ experiences about implementing in text conversations. To answer the purpose of this study empirical material was gathered through qualitative interviews with eight teachers and eleven pupils in a municipality in northern Sweden. The result shows that teachers perceive their form of text conversations as a conversation about a text, which they have read together, were different models are applied and open questions are asked. The pupils have some partial statement about the implementation of text conversations where some has the same idea about text conversations as the teachers. Other pupils say that the implementation of the text conversations are conversations about individually read texts, or conversations about how fictions should be written. The results also show pupils’ and teachers’ experiences about how text conversations can help to increase reading comprehension. The pupils believe that the text conversations can increase the understanding about a text by listen to other classmates’ thoughts about the text. The teachers mention several benefits with text conversations during the interviews. Some benefits they mention is that the vocabulary can be improved, the interest in reading grows and they develop a critical thinking and starts to use each other as resources for increased learning. Conclusions that can be made from this study is that text conversations about fiction can be perceived different in differently ways, and that text conversations are important to increases the reading comprehension. Validerat; 20160628 (global_studentproject_submitter)